Hubungan Motivasi Belajar dengan Hasil Belajar IPS Siswa Kelas IV - Sri Esterina; Dina Anika Marhayani; Mertika Mertika (Jurnal Pendidikan Ilmu Pengetahuan Sosial (JPIPS), 2022)
The purpose of this study is 1) to describe students' learning motivations. 2) to describe the student's learning outcomes. 3) To find out how much the relationship between student learning motivation and student learning outcomes. This research method is a correlation research with quantitative approaches. The data analysis technique used is Pearson Product Moment Correlation (PPM). The results showed that, 1) the level of motivation to learn in natural resource utilization materials wisely is classified as high based on the calculation of the percentage of student grades with an overall average of 79.24. 2) Students' learning outcomes on natural resource utilization materials wisely are classified as high with an overall average of 86.24. So from the results of research that has been done there is a relationship between learning motivation and the results of learning IPS cognitive realm in the material utilization of natural resources wisely.